Effects of Bisphenols on Testicular Steroidogenesis - Barbagallo, Federica; Condorelli, Rosita A.; Mongioì, Laura M.; Cannarella, Rossella; Aversa, Antonio; Calogero, Aldo E.; La Vignera, Sandro (Frontiers in Endocrinology, 2020)
Over the last decades, the adverse effects of human exposure to the so-called “endocrine disruptors” have been the subject of scientific debate and media interest, with great concern for the toxicity on reproductive function. Bisphenols are synthetic chemicals, widely used in the manufacture of hard plastic products. Bisphenol A (BPA) is among the best known environmental toxicants proven to be related to the impairment of male reproductive function and other health problems. BPA is known to migrate from packaging materials into foodstuffs and liquids. Consumer concern resulted in “BPA free” products and in the gradual development of a number of bisphenol analogs (BPA-A) to replace BPA in several applications. However, these other bisphenols derivatives seem to have effects similar to those of BPA. BPA can exhibit weak estrogenic and antiandrogenic proprieties. It interferes with the hypothalamic-pituitary-testicular axis and modulates the gene expressions and enzyme activities involved in steroidogenesis. In addition, it also appears to be involved in DNA methylation. The antiandrogenic properties of BPA have been described in various experimental animal studies. However, the evidence on humans remains ambiguous. Contradictory outcomes may depend on several factors including experimental design, BPA dose, timing and route of exposure and other confounding factors. The effects of BPA appear to be most relevant during development. BPA has been proposed to influence fetal testis development and predispose to testicular dysgenesis syndrome. This includes anatomical abnormalities identified at birth, such as cryptorchidism and hypospadias, but also disorders that occur in adulthood, including testicular tumors, hypogonadism and/or infertility. This review aims to summarize the evidence on the relationship between BPA and testicular function, focusing on its effects on testicular steroidogenesis.